Coronary microvascular dysfunction beyond microvascular obstruction in ST‐elevation myocardial infarction: Functional and clinical correlates. (6th May 2021) - Locorotondo, Gabriella; Galiuto, Leonarda; Porto, Italo; Fedele, Elisa; Paraggio, Lazzaro; Rebuzzi, Antonio G.; Crea, Filippo
Abstract: Objectives: To retrospectively characterize clinical predictors and impact on left ventricular (LV) ejection fraction (EF) of microvascular dysfunction (MVD) beyond microvascular obstruction (MVO), in 49 consecutive patients (58 ± 11 years), with successfully treated ST‐elevation myocardial infarction. Methods: By myocardial contrast echocardiography, MVD was considered as myocardial segments with delayed/patchy opacification, while MVO as areas without any opacification. Both MVD and MVO were planimetered and expressed as percentage of total LV wall area. Patients were divided into tertiles of MVO: I (MVO 0%), II (MVO 4–17%), and III (MVO 18–38%) groups. Cardiac troponin T (cTnT) values obtained at admission and at peak were considered for analysis. Results: MVD correlated inversely with EF in groups I and II (p = 0.025, p = 0.019, respectively), but not in group III. MVD was independently predicted by cTnT on admission (β = 1.85; 95%CI = 0.46–3.24, p = 0.011) and female sex (β for male sex = −14.46; 95% CI = −27.96–0.95), while MVO by anterior MI (β = 0.57; 95% CI = 0.26–0.88, p = 0.008) and peak cTnT (β = 0.97; 95%CI = 0.57–1.38, p < 0.001). Altogether, MVD plus MVO predicted EF (β = −0.18; 95%CI = −0.28‐‐0.07, p = 0.002). Conclusions: Even in patients with limited amount of MVO, EF may be impaired by MVD. MVO and MVD have different predictors, which probably reflect their different pathogenesis.